Analysis of Student’s Online Shopping Behaviour: A Focus Study in UTHM New Campus - Che Him, Norziha; Jusof, Nur Diyana; Ahmad Mukimin, Rizqi Quroti A’yun; Yusof, Yusliandy (Enhanced Knowledge in Sciences and Technology, 2021)
Online shopping becomes one of the favourite channels among university students in spending their money nowadays which include most of the Malaysian community especially during the current pandemic, Corona Virus (COVID-19). Everyone agrees that this activity could reduce the time constraints where some money could be saved with a possible discount offered due to the certain event. It’s also allowed them as a customer to search for the best and desired products and services with better prices, better options and better offers for various choices. This study aims to analyse student’s online shopping behaviour in a new Universiti Tun Hussein Onn Malaysia (UTHM) Campus. The questionnaire was spread to 385 respondents by using convenience sampling methods online such as e-mail and application Whatsapp to the Faculty of Applied Sciences and Technology (FAST), Faculty of Engineering Technology (FTK) and Centre of Diploma Studies (CEDS). There are three objectives which are to analyse student’s preferred way of buying a product (comparison among online shopping and retail store), later to investigate factors influence student’s online shopping behaviour by using the binary logistic model and finally to identify the student’s satisfaction level toward online shopping. Overall, the association of the dependent variable and independent variable were determined through the Chi-Square Test. It shows that all variables in this study have a significant relationship with gender (p-value < 0.05), except for variables Frequency Of Buy From Online Shopping and Preferable Place For Online Shopping. A binary logistic model was built from the value of Chi-Squared with the significant factor that influenced the behaviour of online shopping of students are Frequency Of Buy From Online Shopping and Preferable Place For The Students To Buy Their Product On Online Shopping. In addition, three types of high satisfaction levels chose by students which are Easy Track Parcel, No Need To Go Out and Easily Choose. Meanwhile, a summary of student’s comments based on the satisfaction level toward university management for delivery courier service where the majority of the students rate the delivery courier in a new UTHM campus only 3 out of 5 due to its inconvenient (most word that used by the students in a comment section) for the students to pick up their parcels when the courier delivered during the afternoon. Next, the frequency of a most chosen words is inconvenient, place, pick, class and time.